PENGUKURAN KINERJA MANAJEMEN DALAM IMPLEMENTASI E–PROCUREMENT UNTUK MEWUJUDKAN GOOD GOVERNMENT GOVERNANCE - Handayani, Nur (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2022)
One form of the Surabaya city government's effort to innovate the procurement of goods and services is to implement an electronic goods and service procurement system, known as E-Procurement. To determine the level of success of the implementation of the new system, it is necessary to conduct a research and analysis in a measurable and in-depth manner. One method that can be used is the Balanced Scorecard, which can measure the level of success of a system from 4 (four) perspectives. Based on the results of the research that has been done, it can be concluded that the E-Procurement system has succeeded in minimizing the constraints that occurred in the previous system. In terms of: (1) the financial perspective of E-Procurment can improve efficiency, effectiveness and accountability of financial statements are met. (2) from the customer perspective, E-Procurement has been able to increase the number of bidders and even attract new participants both from within and outside Surabaya. (3) internal business process perspective, E-Procurement is able to innovate that can eliminate the constraints that occurred in the previous system. (4) from a growth and learning perspective, E-Procurement is able to improve the quality and quality of human resources so that from these qualified human resources positive feedback will be obtained for the improvement of this E-Procurement system in the future. In terms of the realization of good government governance, the implementation of E-Procurement is a manifestation of the Surabaya city government's commitment to serving the community, in the process of procuring government goods and services so that they are free from corruption, collusion and nepotism (KKN) practices.